2019
DOI: 10.1186/s12889-019-7042-4
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion and exclusion of people with mental illness in Timor-Leste: a qualitative investigation with multiple stakeholders

Abstract: Background: Social inclusion is a human right for all people, including people with mental illness. It is also an important part of recovery from mental illness. In Timor-Leste, no research has investigated the social experiences of people with mental illness and their families. To fill this knowledge gap and inform ongoing mental health system strengthening, we investigated the experiences of social inclusion and exclusion of people with mental illness and their families in Timor-Leste. Methods: Eighty-five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…Evidently, the prevalence of MDs, determined by age, gender, marital status, ethnicity socioeconomic status, rural residents, migration and displacement, unemployment, poverty, associated physical diseases, life events, disastrous wars, and conflicts varies across the world and is on the rise globally [32][33][34][35][36][37] evidenced by Mosque leaders who perceived common occurrence of MDs in Saudi Arabia. Despite global concerted efforts to improve the image of patients with MDs, stigma, negative attitudes, social exclusion, being dangerous to society, and discrimination contingent on multiple factors still persist against mentally ill population around the world and our study supported this notion [38][39][40][41][42][43]. Unlike family therapy and family and socio-religious supports that mediate protective role [44][45][46], unhealthy family interactions embedded in unhealthy criticisms, over-involvement and hostile attitude towards mentally ill patients tend to worsen their condition, cause relapse, acute psychotic decompensation, rehospitalization and poor outcome [47,48] that partly substantiated by the present online survey.…”
Section: Discussionsupporting
confidence: 74%
“…Evidently, the prevalence of MDs, determined by age, gender, marital status, ethnicity socioeconomic status, rural residents, migration and displacement, unemployment, poverty, associated physical diseases, life events, disastrous wars, and conflicts varies across the world and is on the rise globally [32][33][34][35][36][37] evidenced by Mosque leaders who perceived common occurrence of MDs in Saudi Arabia. Despite global concerted efforts to improve the image of patients with MDs, stigma, negative attitudes, social exclusion, being dangerous to society, and discrimination contingent on multiple factors still persist against mentally ill population around the world and our study supported this notion [38][39][40][41][42][43]. Unlike family therapy and family and socio-religious supports that mediate protective role [44][45][46], unhealthy family interactions embedded in unhealthy criticisms, over-involvement and hostile attitude towards mentally ill patients tend to worsen their condition, cause relapse, acute psychotic decompensation, rehospitalization and poor outcome [47,48] that partly substantiated by the present online survey.…”
Section: Discussionsupporting
confidence: 74%
“…With regard to the perceived attitudes of community members towards disability, the findings of this study contrast with those of other studies conducted in Malawi [35,39], in that our participants generally reported that their community was supportive, and that even those who did experience social exclusion because of their disability did not find it affected their access to health care. Some studies have found that stigmatisation and discrimination at the community level discourages people with disabilties from attending health services [40,41]. It might be inferred, therefore, that the feelings of exclusion and restricted freedom described by some of our participants could 'delay the decision the seek care' but, when asked, our participants denied that this was the case.…”
Section: Discussion Of the Attitudinal Barriersmentioning
confidence: 74%
“…Practically, there was no service user organisation to facilitate individual and collective engagement of Timorese people with mental illness, who have limited opportunities to develop advocacy skills due to their exclusion from society and public services (i.e. education, social welfare, legal) [36]. Socially, Timorese norms do not legitimise the role of people with mental health problems in decision making [43], particularly for high level national policies, as has been found in other LMICs [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…This latter frame may focus on reducing the community-based and systemic exclusion confronted by Timorese people with psychosocial disabilities (e.g. exclusion from education, employment, confinement and physical restraint) [36] and the combating of the biomedical model of mental illness, which is a well-documented challenge to social participation for people with mental health problems [45][46][47]. Disability rights have been a powerful impetus for uniting people with psychosocial disabilities in some countries in the Asia Pacific [10], and there is already a strong disability sector in Timor-Leste for people with physical and sensory disabilities [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation